2018
DOI: 10.1007/s00264-018-3768-3
|View full text |Cite
|
Sign up to set email alerts
|

Is there any difference between open and arthroscopic treatment for osteochondritis dissecans (OCD) of the humeral capitellum: a systematic review and meta-analysis

Abstract: Purpose We present a systematic review of the recent literatures regarding the arthroscopic and open technique in fragment fixation for osteochondritis dissecans (OCD) of the humeral capitellum and an analysis of the subjective and objective outcomes between these two procedures. Methods PubMed and EMBASE were reviewed for suitable articles relating to fragment fixation for OCD, both open and arthroscopic. We included all studies reporting on the clinical outcomes of these two procedures that were published in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 39 publications
1
23
0
2
Order By: Relevance
“…In einem systematischen Review zeigten sich nach einem halben Jahr 75-100 % der refixierten Fragmente konsolidiert. Ohne einen Niveauunterschied zu messen, konnten den Ergebnissen folgend, bis zu 91,4 % wieder sportlich aktiv werden [28]. werden Chondrozyten meist aus der Femurkondyle außerhalb der Belastungszone explantiert, im Labor gezüchtet und nach einigen Wochen replantiert.…”
Section: Fragmentrefixationunclassified
“…In einem systematischen Review zeigten sich nach einem halben Jahr 75-100 % der refixierten Fragmente konsolidiert. Ohne einen Niveauunterschied zu messen, konnten den Ergebnissen folgend, bis zu 91,4 % wieder sportlich aktiv werden [28]. werden Chondrozyten meist aus der Femurkondyle außerhalb der Belastungszone explantiert, im Labor gezüchtet und nach einigen Wochen replantiert.…”
Section: Fragmentrefixationunclassified
“…In this study, there are three meta-analysis papers. Lu et al presented a systematic review of ten recent studies regarding the operative techniques for osteochondritis dissecans (OCD) of the humeral capitellum [33]. They found that arthroscopic lesion debridement with fragment fixation can treat unstable OCD as good as, if not better than open procedure.…”
Section: Yingze Zhangmentioning
confidence: 99%
“…While the exact mechanism for OCD lesion formation remains unclear, a multi-factorial etiology-altered biomechanics, repetitive microtrauma, localized ischemia, and a genetic predisposition-is most likely [4][5][6][7]. When specifically assessing OCD of the capitellum, repetitive compression at the radiocapitellar articulation from either excessive valgus or axial loading is believed to play the predominant role [8]. Therefore, while capitellar OCD lesions have been described in athletes playing handball, basketball, kendo, lacrosse, and motocross, it is the overhead athlete-baseball players and gymnasts-who are most commonly affected by this disorder [3,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…When specifically assessing OCD of the capitellum, repetitive compression at the radiocapitellar articulation from either excessive valgus or axial loading is believed to play the predominant role [8]. Therefore, while capitellar OCD lesions have been described in athletes playing handball, basketball, kendo, lacrosse, and motocross, it is the overhead athlete-baseball players and gymnasts-who are most commonly affected by this disorder [3,8,9]. In fact, the highest reported incidence is in youth baseball players ranges between 1 and 7% [10][11][12].…”
Section: Introductionmentioning
confidence: 99%